A monoclonal antibody-based sandwich ELISA for measuring canine Thymidine kinase 1 protein and its role as biomarker in canine lymphoma - Sharif, Hanan; Saellström, Sara; Kolli, Bhavya; Jagarlamudi, Kiran Kumar; Wang, Liya; Rönnberg, Henrik; Eriksson, Staffan (Frontiers in Veterinary Science, 2023)
Dogs play an important role in society, which increased during the covid epidemics. This has led to a much higher workload for the veterinarians. Therefore, there is a need for efficient diagnostic tools to identify risk of malignant diseases. Here the development of a new test that can solve some of these problems is presented. It is based on serum Thymidine Kinase 1 (TK1), which is a biomarker for cell proliferation and cell lysis. Anti-TK1 monoclonal antibodies were produced against two different epitopes, the active site of the TK1 protein and the C-terminal region of canine TK1. The antibodies were developed with hybridoma technology and validated using dot blot, Quartz Crystal Microbalance (QCM) technology, western blots, immunoprecipitation (IP) and enzyme-linked immunosorbent assay (ELISA). Clinical evaluation of Canine TK1 ELISA was done by using sera from 131 healthy dogs and 93 dogs with lymphoma. The two selected Anti-TK1 monoclonal antibodies have Kd values in the range of 10-9 M and further analysis with dot and western blots confirmed the high affinity binding of these antibodies. A sandwich Canine TK1 ELISA was developed using the anti-TK1 antibodies, and TK1 concentrations in serum samples were determined using dog recombinant TK1 as a standard. Serum TK1 protein levels were significantly higher in dogs with lymphoma compared to those in healthy dogs (p<0.0001). Receiver operating curve analysis showed that the canine TK1-ELISA obtain a sensitivity of 0.80, at a specificity of 0.95. Moreover, the Canine TK1 ELISA has a positive predictive value (PPV) of 97%, and the negative predictive value (NPV) of 83%, reflecting the proportion of test results that are truly positive and negative. Furthermore, Canine TK1 ELISA had significantly higher capacity to differentiate dogs with T-cell lymphoma from those with B-cell lymphoma compared to earlier used TK1 activity assays. These results demonstrate that the Canine TK1 ELISA can serve as an efficient tool in the diagnosis and management of dogs with lymphomas.